2016
DOI: 10.1155/2016/5428581
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Approach to Evaluate the Morphological Patterns of Soft Palate in Oral Submucous Fibrosis Patients: A Digital Cephalometric Study

Abstract: Oral submucous fibrosis (OSMF) is a chronic insidious disease affecting mucosa and submucosa of oral cavity and soft palate. The present study aimed to evaluate the morphology of soft palate in normal individuals and OSMF patients using lateral cephalometry and to compare and correlate these variants of soft palate with different stages of OSMF. 100 subjects were included in the study, who were divided into two groups. Group I included 50 subjects with clinical diagnosis of OSMF and Group II included 50 normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
1
5
2
Order By: Relevance
“…Stage 3 patients had Type 6 the most common, followed by Type 3 and Type 1. Type 4 was commonly observed among OSMF patients in contrast to our study (Raja Lakshmi et al, 2016).…”
Section: Type Of Soft Palate Among Osmf Patients and Control Groupcontrasting
confidence: 94%
See 1 more Smart Citation
“…Stage 3 patients had Type 6 the most common, followed by Type 3 and Type 1. Type 4 was commonly observed among OSMF patients in contrast to our study (Raja Lakshmi et al, 2016).…”
Section: Type Of Soft Palate Among Osmf Patients and Control Groupcontrasting
confidence: 94%
“…These studies also showed that crook shaped type is the least typical soft palate which was not a finding in our study. Type 2 was the most common soft plate type in a study by Raja Lakshmi et al, (2016) and Praveen et al According to More et al butt type of morphology were most common in healthy individuals (More et al, 2015).…”
Section: Type Of Soft Palate Among Osmf Patients and Control Groupmentioning
confidence: 92%
“…We can say that CBCT is more useful to show length and width changes in OSMF patients. Findings of length, width & angle changes were in accordance with Raja Lakshmi et al, 16 Tekchandani et al 1 Angle was not measured in their study. Tekchandani et al 1 compared clinical and histological grades of OSMF with radiographic variables.…”
Section: Discussionsupporting
confidence: 83%
“…Anatomical deficiencies, such as cleft palate, are known to cause velopharyngeal insufficiency, or the inability of the velopharyngeal mechanism to completely close off the oral cavity from the nasal cavity. The literature has shown that velar shape may be pertinent to patient health and well-being, specifically relative to obstructive sleep apnea (OSA)1 and oral submucous fibrosis 2345…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies have applied qualitative velar classifications to analyze lateral cephalograms 12347891011121314. For the majority of these studies, the most common velar shape was “leaf,” and no significant difference in shape was reported based on sex or age 1791215.…”
Section: Introductionmentioning
confidence: 99%